A chiral decorated metal-isonicotinate coordination polymer - Timothy J. Prior (2018)
The isostructural coordination polymers, M(isonicotinate)(tyrosinate) (H2O)2[M = Co or Ni] have been synthesized by microwave-assisted hydrothermal methods. These compounds crystallize in the non-centric space group P21. At 290 K, for the cobalt analogue the unit cell parameters are a = 6.0658(6), b = 15.540(2), c = 9.1328(9) Å, β = 107.052(7), V = 823.05(16) Å3; for the nickel compound a = 6.0946(8), b = 15.443(2), c = 9.1202(11) Å, β = 107.803(10), V = 817.28(19) Å3. The structure contains linear chains with composition [M(isonicotinate)]∞in which the isonicotinate is arranged head-to-tail and binds to octahedral cations through both pyridine and monodentate carboxylate functions. At each metal centre the coordination is completed by two cis water molecules and tyrosinate that chelates to the metal centre through monodentate carboxylate and amine groups. The chains run parallel to the crystallographic [101] direction. Between the chains there is extensive hydrogen bonding between bound water and carboxylate groups. The cobalt compound loses water upon heating above room temperature and continues to lose mass in ill-defined steps upon further heating; in contrast the nickel compound loses mass in well-defined steps. Graphical Abstract: An achiral one dimensional chain can be decorated with the chiral auxiliary tyrosine to produce a homochiral coordination polymer.© 2013 Springer Science+Business Media New York.